Philippe Ariés, Morir en occidente: desde la Edad Media hasta nuestros días, trad. Víctor Goldstein, Adriana Hidalgo editora, Buenos Aires, 2007. ISBN-13: 978-987-9396-38-4. 270 pp. - Mendoza, José María Felipe (2009)
Fil: Mendoza, José María Felipe.